Assessing Fungal Diversity in a Tropical Urban River Through Environmental DNA Metagenomics - Sukma, Kenia Permata; Widana, Agus; Depi, Sinta; Nabila, Dinah (Jurnal Biologi Tropis, 2025)
Fungal community composition and abundance in river ecosystems are highly responsive to hydrological processes, terrestrial runoff, and anthropogenic pressures, making riverine fungi a sensitive biological indicator of water quality and overall ecological condition. This study employed Oxford Nanopore-based shotgun metagenomics to characterize fungal communities from two segments in Cikapundung River, Indonesia, differing in human impact. Water samples were vacuum-filtered, DNA was extracted and sequenced, and taxonomic profiles were generated. Results revealed that both sites were dominated by plant-associated Ascomycota, particularly several Pyricularia species, indicating strong terrestrial-aquatic connectivity driven by riparian plants and terrestrial plant debris entering the river. Cikapundung B site exhibited higher fungal abundance and diversity than Cikapundung A site, while Bray-Curtis PCoA showed clear compositional separation between sites, reflecting spatial ecological stress. Although a considerable proportion of reads remained unclassified due to limited fungal reference genomes, dominant taxa provided ecologically meaningful insights. These findings demonstrate that fungal environmental DNA could indicate environmental conditions in tropical urban rivers and highlight the potential and limitation of metagenomic approaches for river health monitoring and watershed management.